Impact of incentive schemes and personality-tradeoffs on two-agent coopetition: A theoretical examination - Chión Chacón, Sergio Julio (2016)
The main purpose of the present paper is to analyze the feasibility of managing coopetition among two given agents in a firm, under a Markovian structure, where the transition probabilities are defined by the incentive schemes for cooperation and competition and the personality-tradeoffs between the two agents. Furthermore, the asymptotic behavior of the model is considered and analyzed through a numerical estimation of the different possibilities. The behavior of the steady state probabilities as a function of the incentive scheme is shown for different possibilities of personality-tradeoffs between the agents. The existence of a Dominant Coopetitive Range, wherein the steady state probability of the coopetition state is higher than the similar probabilities of the cooperation and competition state, is shown to exist for some types of personality-tradeoffs. The State Dominance Mapping is found, and it is shown that the locus of the types of personality-tradeoffs in which coopetition is prevalent is quite narrow. Lastly, the probabilities of remaining in a specific state of cooperation, competition, and no coopetition are found, for the Coopetition Locus. Our results indicate that the possibilities for managing coopetition through incentive schemes are quite narrow and that an active management of interpersonal relationships in the firm is required. The paper also aims to introduce a general framework for the analysis of coopetition at the micro level, by explicitly considering coopetition and not merely a treatment of alternating behavior between pure cooperation and pure competition.